Neonatal acute osteomyelitis and septic arthritis as adverse effect of intramuscular injection - Mohamed, Mossad Abdelhak Shaban; Hasan, Taufiq Hidayat; Abdelhalim, Abdelbaset Taher (ECronicon, 2018)
We reported 19 days old baby boy in Nicu, Hera general hospital with the presentation of fever, crying, limited and painful movement of right lower limb. He had history of high fever for seven days that was treated by intramuscular injection of third generation cephalosporin. Along with complete septic profile urgent ultrasound and MRI established diagnosis of Osteomyelitis of right femoral head and proximal metaphysis, right hip septic arthritis with marked intra capsular collection and there is small abscess in the left thigh. Urgent surgical drainage was done after diagnostic joint tapping and the patient finished 6 weeks courses of antibiotics. In spite of good clinical, laboratory and radiological improvement of inflammatory process, true burden of morbidity started in the form of shortening right lower limb and same side hip dislocation.